Intersectional Analysis of the Labour Market Impacts of COVID: The Triple-Whammy of Females, Children, and Lower Skill - Tony Fang; Morley Gunderson; Viet Hoang Ha; Hui Ming (Institute of Labor Economics (IZA), 2024)
We employ a Gender-Based Plus (GBA+) and intersectionality lens to examine the triple whammy of the differential effect of Covid on the trifecta of being female, lower-skilled and facing a motherhood penalty from school-age children. We use a difference-in-difference framework with Canadian Labour Force Survey data to examine the differential effect of two waves of Covid on three outcomes: employment, hours worked, and hourly wages. We find that the trifecta of being female in a lower-skilled occupation and with school-age children is associated with lower employment, hours worked and wages in normal times compared to males in those same situations. As well, such females face the most severe adjustment consequence from major shocks like Covid, with that adjustment concentrated on the extensive margin of employment, and it is restricted to the immediate First Wave and not on a subsequent Omicron wave.
Keywords: J13; J16; J64; J71; J78; 330; trifecta; difference-in-Difference; labour market impacts; Omicron; COVID-19; woman; lower-skilled jobs; motherhood penalty